TMT diversity and innovation ambidexterity in family firms: The mediating role of open innovation breadth. Issue 4 (29th November 2019) - Röd, Irina
Abstract : Purpose: Family firms that simultaneously engage in multiple levels of innovation – incremental and radical – are likely to enjoy performance advantages across generations. The purpose of this paper is to research under which management conditions (i.e. top management team (TMT) diversity in terms of generational or non-family involvement) family firms are more likely to achieve innovation ambidexterity. Also, the paper addresses the mediating role of open innovation (OI) breadth in this relationship. Design/methodology/approach: A large cross-sectional sample of 335 small- and medium-sized family firms is used. The hypotheses were tested in a mediation model. The relationship between TMT diversity and ambidexterity is measured using a binominal regression analysis, the one between TMT diversity and OI breadth using a Tobit model. Findings: Drawing on the family firm upper echelon perspective, the results indicate that TMT diversity induced through external managers and multiple generations is positively related to innovation ambidexterity. As the mediation analysis reveals, the relationship can be explained by the higher propensity of diverse TMTs to get involved in OI breadth. The findings add to the discussion on family firm heterogeneity and its influence on different kinds of innovation. Originality/value: So far, few studies have been concerned with ambidextrous family firms. Contrary to their reputation, this study identifies family firms as radical as well as open innovators. As such, this research takes account not only of the heterogeneity of family firms, but also of the heterogeneity of family firm innovation.